The impact of periodontal disease and dental cleaning procedures on serum and urine kidney biomarkers in dogs and cats. - Jean A Hall (Public Library of Science (PLoS), 2021)
The objective of this study was to evaluate the benefits and inherent risks of dental cleaning procedures, based on serum and urine biomarkers for kidney function and tissue damage, in dogs and cats. Thirty-one asymptomatic, mostly older dogs (14 neutered male and 17 ovariohysterectomized female dogs of various breeds between 3 and 14 years old) and cats (19 neutered male and 12 ovariohysterectomized female domestic short hair cats between 2 and 16 years old) diagnosed with periodontal disease on physical exam, and recommended by their veterinarian to have dental cleaning under general anesthesia were evaluated in a prospective study. Serum and urine samples were collected from dogs and cats 1 week before, 6 hours after, and again 1 week after the dental cleaning procedure. Samples were analyzed for biomarkers of kidney function [serum creatinine (Cr), symmetric dimethylarginine (SDMA), and blood urea nitrogen (BUN), and urine for specific gravity (USG) and protein:creatinine (UPC) ratio]. A panel of biomarkers for renal tissue damage was also assessed [serum β-aminoisobutyric acid (BAIB), and urine cystatin B and clusterin]. Samples collected one week before dental cleaning procedures showed that increased age and severity of dental disease were linked to abnormal kidney function biomarker values (age: elevated SDMA and Cr concentrations and isosthenuric USG values; disease severity: elevated UPC ratios) as well as elevated urine cystatin B and clusterin concentrations. Directly after the dental cleaning procedure, an increased number of cats with elevated SDMA concentrations was observed (specifically in cats with longer duration of dental procedures). Extended duration of dental procedures (≥60 min) was linked to increased urine cystatin B and clusterin concentrations, whereas shorter duration procedures was linked to decreased urine cystatin B and clusterin. Higher SDMA concentrations persisted in cats one week after the dental cleaning procedures and were linked to elevated UPC ratios one week before cleaning procedures. In conclusion, the results of this study indicate a link between severity of dental disease, renal tissue injury, and impaired renal function. Longer duration dental procedures in cats may carry inherent risks of kidney injury and impaired renal function.